26 Investigating boron neutron capture therapy for the treatment of glioblastoma - Bethany Mackinnon (Neuro-Oncology, 2026)
Abstract Introduction With an average survival of 12-18 months, glioblastoma is the most commonly diagnosed malignant brain tumour in adults. Despite treatment advances, survival outcomes have shown minimal improvements over the past decades. Persistent treatment resistance, and disease recurrence, highlight the need for alternative, more effective, therapies to be explored. Driven by advances in accelerator-based neutron sources and next-generation boron compounds, boron neutron capture therapy (BNCT) has re-emerged as a promising alternative therapy for glioblastoma. BNCT involves loading tumour cells with boron-10 and irradiating the tumour with thermal neutrons, which releases high-LET particles that deposit their energy over a very short distance, selectively killing tumour cells while sparing healthy tissue. With Birmingham hosting the UK’s first and only neutron source, this work is well positioned to generate mechanistic insights that will drive BNCT development for effectively treating glioblastoma. Methods Human glioblastoma cell lines were treated with a panel of boron-10 compounds. MTTs, clonogenics, and spheroid growth assays were performed to assess toxicity, and baseline X-ray radiosensitisation. These experiments have been replicated with neutrons to evaluate BNCT efficacy. Boron compound uptake was measured using ICP-MS. LAT1 was overexpressed using a LIC-assembled plasmid and knocked down using siRNA. Results Across all boron-10 compounds, minimal toxicity was observed on glioblastoma cells, and as expected no measurable radiosensitisation occurred with X-rays. In contrast, significant glioblastoma cell killing was observed in BNCT reactions where boron uptake was shown. LAT1-dependence studies are ongoing. Conclusions This research establishes a strong foundation for establishing BNCT as a more effective treatment for glioblastoma, and provides a clear pathway for evaluating its optimal efficacy in combination with other targeted drugs/inhibitors. Future work will focus on evaluation of other glioblastoma-specific boron-10 compounds.